Peran komunikasi interpersonal dalam membangun lingkungan belajar inklusif bagi siswa disabilitas - Zakri, Rahmania; Sarmiati; ahmad, Asmawi (Education and Social Sciences Review, 2025)
Inclusive education is a crucial foundation for providing students with disabilities equal and appropriate educational rights. However, its successful implementation greatly depends on interpersonal communication between teachers and students. This study aims to analyze the role of teachers' interpersonal communication as a key factor in creating an effective and inclusive learning environment. Using a constructivist paradigm and a qualitative case study approach, this study explores in depth the interactions between teachers and students with disabilities in an inclusive classroom environment (with a case study context at the SMP Pembangunan Laboratorium Universitas Negeri Padang). Data were collected through observation and in-depth interviews, with Social Penetration Theory used as the main analytical framework. The results show that effective interpersonal communication and optimization of the teaching and learning process for students with disabilities begin with a personal approach by teachers that is oriented towards building trust and a sense of security. This approach facilitates self-disclosure by students in interactions and learning. Appropriate communication, characterized by the establishment of strong trust, contributes significantly to creating positive relationships and a conducive learning environment. This study concludes that mastery of interpersonal communication based on a personal approach is not merely a method, but a vital foundation for creating supportive and successful interactions in the context of inclusive education. These findings provide theoretical implications regarding the role of social penetration in the context of inclusive education.